2012
DOI: 10.1098/rsta.2011.0600
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth as an excitable medium

Abstract: Crystal growth has been widely studied for many years, and, since the pioneering work of Burton, Cabrera and Frank, spirals and target patterns on the crystal surface have been understood as forms of tangential crystal growth mediated by defects and by twodimensional nucleation. Similar spirals and target patterns are ubiquitous in physical systems describable as excitable media. Here, we demonstrate that this is not merely a superficial resemblance, that the physics of crystal growth can be set within the fra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Therefore, it is plausible that the patterns observed during the formation of nacre are also the result of a reaction‐diffusion self‐assembly process. Or as was claimed by Cartwright et al, the physics of crystal growth can be set within the framework of the BZ reaction in 3D. However, it is important to note that while the contrast seen in the original BZ patterns in Figures i,j was attained due to differences in chemical composition, the contrast obtained in nacre, in Figures f,h, is merely the consequence of the imaging method in scanning electron microscopy.…”
Section: Evidence Of Spontaneous Growthmentioning
confidence: 73%
See 1 more Smart Citation
“…Therefore, it is plausible that the patterns observed during the formation of nacre are also the result of a reaction‐diffusion self‐assembly process. Or as was claimed by Cartwright et al, the physics of crystal growth can be set within the framework of the BZ reaction in 3D. However, it is important to note that while the contrast seen in the original BZ patterns in Figures i,j was attained due to differences in chemical composition, the contrast obtained in nacre, in Figures f,h, is merely the consequence of the imaging method in scanning electron microscopy.…”
Section: Evidence Of Spontaneous Growthmentioning
confidence: 73%
“…Wada was also the first to make the analogy to the BCF model emphasizing that the spiral pattern can be well explained by Frank's screw dislocation theory describing the spiral growth of single crystals. This line of thought was investigated further much later by Cartwright, Checa and colleagues in a series of studies . They proposed a simplistic mathematical treatment to model the morphogenesis of the patterns observed in the growth front of nacre inspired by the BCF model.…”
Section: Evidence Of Spontaneous Growthmentioning
confidence: 99%
“…During a time step, nucleation has a probability of 1 to occur at all the cells where the condition (2.2) is satisfied. In previous work with a numerical model of this type, we had a nucleation probability, a small number, typically 10 −3 , so that nucleation would be a rare event [15,16]. In the present case, we have removed this parameter, with the objective to have a more elegant model; to eliminate as much complexity as possible while still being able to reproduce all the patterns observed.…”
Section: Modelmentioning
confidence: 99%
“…Common to these varied systems is that they are excitable media: they all have a threshold in some parameter, below which the system returns quickly to its resting state, but above which it undertakes a large excursion before doing so, and then has a refractory period during which the system is unresponsive to further perturbations. Some of us developed a model of Burton–Cabrera–Frank dynamics as an excitable system, and showed that it could be applied both to crystal growth [15] and to liquid crystals growing layer by layer as they do in the formation of the mother-of-pearl produced by molluscs [16]. In the present work, we show that a version of this coupled-map lattice excitable medium model explains how the complex structures seen in Tetragonula combs emerge from simple behavioural rules.…”
Section: Introductionmentioning
confidence: 99%
“…To give just one example of the power of such a comprehensive understanding, excitability [23] is a general mechanism that produces spiral and target patterns at various scales in a great variety of natural systems in physics, chemistry, biology and beyond, from the Belousov-Zhabotinsky reaction [28][29][30][31] to the myocardial tissue of the heart undergoing ventricular fibrillation. It turns out that the Burton-Cabrera-Frank mechanism of crystal growth [32] is one more instance of an excitable medium [33]; this mechanism of excitability functions in the self-assembly of crystals themselves, and hence the spiral and target patterns characteristic of excitable media appear at the molecular scale on the faces of growing crystals.…”
Section: (A) Generalized Crystallographymentioning
confidence: 99%